Transmedia storytelling and Lost path to success - Matsunaga Sasaki, Daniella (2012)
This thesis analyses the transmedia storytelling strategy applied to promote the TV series Lost. As transmedia storytelling one may understand it as a story told throughout different media, with exclusive content pointing back to the main narrative, working as a potential new audience entry-point. “Which transmedia elements of the Lost formula could be transferable to other cases?” is the research question proposed and in order to answer it, all Lost transmedia events and other marketing elements are discussed and analysed. Alternate Reality Games (ARG) were the main part of this transmedia strategy, counting five in total. Added to ARG, there were mobisodes/websodes and a pseudo-documentary. Beside the transmedia, the following marketing elements are also analysed: a video game, a web game-style narrative, official podcasts, and DVDs/Blu-rays. Fandom is also discussed, as it is inevitable to talk about a TV show success without touching the subject. Transmedia elements are analysed based on the very transmedia storytelling concept, (a) the medium utilised; (b) strategy applied/objective(s); (c) how much it affected the viewser’s knowledge compared to the main narrative; (d) where did the transmedia event led the viewser; and finally, (e) if this transmedia event could actually work as an inviting entry-point to new audience. Based on the mentioned characteristics, it is possible to see that Lost transmedia elements were indeed successful and it could be applied, with appropriated changes, to other cases taking in consideration their particular features.